3D printing magnesium-doped wollastonite/β-TCP bioceramics scaffolds with high strength and adjustable degradation. Issue 6 (May 2016) - Shao, Huifeng; He, Yong; Fu, Jianzhong; He, Dongshuang; Yang, Xianyan; Xie, Jiajun; Yao, Chunlei; Ye, Juan; Xu, Sanzhong; Gou, Zhongru
Abstract: Mechanical strength of bioceramic scaffolds is a problem to treat the load bearing bone defects. We developed the Mg-doping wollastonite (CSi-Mg)-based scaffolds with high strength via 3D printing technology. The effect of pore size, β-tricalcium phosphate (β-TCP) content ( x %), and heating schedule on the strength of scaffolds were investigated systematically. Incorporation of β-TCP could readily adjust the sintering properties of the CSi-Mg scaffolds and the scaffolds with high (20–30%) and low (10–20%) β-TCP possess much high strength (80–100 MPa or 120–140 MPa) after undergoing one- or two-step sintering. Meanwhile, the CSi-Mg/TCP x ( x = 10, 20) with medium-pore (∼320 μm) had over 100 MPa in compression and ∼52% in porosity. In particular, the composite scaffolds maintained appreciable strength (over 50 MPa) after immersion in Tris buffer for a long time stage (6 weeks). These findings demonstrate that the CSi-Mg/TCP x scaffolds are promising for treating some challengeable bone defects, especially for load-bearing bone repair.